2020
DOI: 10.1177/1078155220951898
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of C677T MTHFR variant but not A1298C in methotrexate-induced toxicity in acute lymphoblastic leukemia

Abstract: Background Methotrexate (MTX) is a key drug in acute lymphoblastic leukemia (ALL) treatment; it inhibits DNA replication by blocking the conversion of 5, 10 Methylenetetrahydrofolate to 5-methylene tetrahydrofolate by methylenetetrahydrofolate reductase (MTHFR). Variants of the Methylenetetrahydrofolate reductase (MTHFR) and MTX related toxicities were largely investigated in several populations, nevertheless, the results are conflicting. Objective This study aimed to assess the prevalence of MTHFR SNVs: C677&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Two of the most investigated polymorphisms within the MTHFR gene are single nucleotide polymorphisms (SNPs) at the mRNA positions 677 (rs1801133) and 1,298 (rs1801131) ( 8 ). However, these findings were mainly found in the patients with rheumatoid arthritis or the hematological malignancies ( 14 16 , 27 ). This is the first report on serious adverse toxic effects of LD-MTX on an EP patient with MTHFR mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the most investigated polymorphisms within the MTHFR gene are single nucleotide polymorphisms (SNPs) at the mRNA positions 677 (rs1801133) and 1,298 (rs1801131) ( 8 ). However, these findings were mainly found in the patients with rheumatoid arthritis or the hematological malignancies ( 14 16 , 27 ). This is the first report on serious adverse toxic effects of LD-MTX on an EP patient with MTHFR mutations.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have shown that severe adverse toxic effects of LD-MTX are associated with polymorphisms of methylenetetrahydrofolate reductase ( MTHFR ) gene, such as MTHFR 677TT and 1298AA ( 8 , 14 16 ), as the polymorphisms of MTHFR gene can decrease the MTX clearance, leading to the metabolite accumulation ( 15 , 17 ). For the patients who had serious adverse toxic effects of LD-MTX, it is essential to consider genetic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 To date, numerous studies have analyzed separately the relationship between the C677T and A1298C polymorphisms of MTHFR and MTX toxicity in ALL, but the conclusions remain controversial. [8][9][10][11] To the best of my knowledge, most of these studies do not analyze haplotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the most investigated polymorphisms within the MTHFR gene are single nucleotide polymorphisms (SNPs) at the mRNA positions 677 (rs1801133) and 1,298 (rs1801131) (8). However, these findings were mainly found in the patients with rheumatoid arthritis or the hematological malignancies (14)(15)(16)27). This is the first report on serious adverse toxic effects of LD-MTX on an EP patient with MTHFR mutations.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have shown that severe adverse toxic effects of LD-MTX are associated with polymorphisms of methylenetetrahydrofolate reductase (MTHFR) gene, such as MTHFR 677TT and 1298AA (8,(14)(15)(16), as the polymorphisms of MTHFR gene can decrease the MTX clearance, leading to the metabolite accumulation (15,17). For the patients who had serious adverse toxic effects of LD-MTX, it is essential to consider genetic abnormalities.…”
Section: Introductionmentioning
confidence: 99%